Influence of the Density of a Forest Combustible Material on the Suppression of its Thermal Decomposition by a Liquid Aerosol; Journal of Engineering Physics and Thermophysics; Vol. 91, iss. 4 - Zhdanova A. O. Alena Olegovna (2018, 2018)
Title screen